PHYSICAL EDUCATION PROFESSIONALS IN FITNESS CENTERS: BODY PAIN AS WORK PERFORMANCE - Alan Camargo Silva; Jaqueline Ferreira (Journal of Physical Education)
ABSTRACT The meanings and definitions related to the body and pain are valued differently by each social group in a specific time in history. Therefore, the main objective of this work was to identify and discuss how Physical Education professionals in a large fitness center work between the “limit” of work performance and body pain. Using the theory and method of the Symbolic Interactionism and the Anthropology of Performance as references, this research consisted of an ethnographic study of Physical Education professionals over ten months between 2012 and 2013. The analyses of the observations recorded in the field diary indicated that the working competence of the Physical Education professionals was in some cases associated with body performance, represented by the capacity to prescribe physical exercises and train on the “limit” of pain.